Genetic testing for cancer risk: is the community willing to pay for it? - Azimatun Noor Aizuddin; Abdul Rahman Ramdzan; Sharifah Azween Syed Omar; Zuria Mahmud; Zarina A. Latiff; Salleh Amat; Keng Wee Teik; Ch’ng Gaik Siew; Haniza Rais; Syed Mohamed Aljunid (MDPI, 2021)
With the increasing number of cancer cases worldwide, genetic testing for familiar cancers seems inevitable, yet little is known on population interest and the monetary value for cancer genetic risk information. The current study aimed to determine the willingness to undergo and pay for cancer genetic testing among the Malaysian population. A self-administered questionnaire was distributed to cancer patients and their family members in the oncology and daycare units in several government hospitals. Of 641 respondents (354 patients, 287 family members), 267 (41.7%) were willing to undergo cancer genetic testing. The median that respondents were willing to pay was USD 48.31 (MYR 200.00) IQR USD 96.91 (MYR 400), while 143 (22.3%) respondents were willing to pay a shared cost with the insurance company. Regression analysis identified independent positive predictors of willingness to pay as respondent’s status as a family member, high education level, and willingness to undergo cancer genetic testing in general, while in patients, female gender and high level of education were identified as independent positive predictors. Generally, the population needs more information to undergo and pay for cancer genetic testing. This will increase the utilization of the services offered, and with cost-sharing practices with the provider, it can be implemented population-wide.